Risk factors of pulmonary embolism in postpartum women - Cui, Min; Wu, Yan; Tong, Shanshan; Feng, Qiang; Qin, Xuewei; Wu, Xue-ling (Frontiers in Medicine, 2025)
IntroductionPulmonary embolism (PE) is a potentially fatal complication, especially in postpartum women.ObjectiveTo explore the risk factors of PE in postpartum women.MethodsA retrospective cohort study consisted of 130 postpartum women with PE (PE Group) and 192 postpartum women without PE (non-PE Group), which were analyzed.ResultsThe PE group was older, with 37.7% having multiple deliveries, and the inter-pregnancy interval was mostly 1–3 years (p < 0.05). The incidence of prophylactic anticoagulation, anemia, prenatal fever, emergency cesarean section, twins, postpartum acute infection, intraoperative bleeding, postpartum hemorrhage, and venous thromboembolism (VTE) was significantly higher in the PE group. Abnormal clinical manifestations and echocardiographic measures were more common (p < 0.05). The levels of creatinine, urea nitrogen, fibrinogen, total protein, and albumin in the PE group were significantly lower, whereas total bilirubin, d-dimer, and B-type Natriuretic Peptide (BNP) were significantly higher (p < 0.05). The ROC curve analysis showed the best cutoff point for d-dimer level within postpartum women was 2.24 mg/L (specificity 90.1%, sensitivity 88.9%). On multivariate analysis, VTE and abnormal echocardiography were independent risk factors for PE (p < 0.05). The d-dimer levels (OR 1.363, 95% CI 1.716–8.907, p = 0.001) were a specific marker for clinical monitoring of PE.ConclusionIt was necessary to strengthen the clinical monitoring of PE-related risk factors in postpartum women, especially in those with VTE, abnormal echocardiography, and a d-dimer level > 2.24 mg/L.